A STUDY ON ONLINE CUSTOMER COMPLAINTS AGAINST THE PARTICIPATION BANKS DURING THE COVID-19 PANDEMIC (Third Sector Social Economic Review, 2021)
As the Covid-19 pandemic has affected many sectors; the banking sector is no exception to this effect. The purpose of this study is to examine the online complaints raised against participation banks during the Covid 19 pandemic process. For this purpose, complaints submitted to the website www.sikayetvar.com, which is one of the largest online complaint platforms in the World, by customers to the Participation Banks operating in Turkey, during February 2021. A total of 300 online customer complaints were analyzed by content analysis, one of the qualitative research methods. Complaints were analyzed under two main themes, namely services and products offered by participation banks, and complaints originating from customer representatives, and sub-categories determined based on these themes. According to the analysis findings, it has been determined that the complaints of the participation bank customers mainly stem from investment transactions, card transactions, account transactions and ATM services, which are included in the product and services category. It is expected that the study will contribute to the literature and participation banking sector due to the limited number of studies on the effects of the Covid-19 Pandemic on participation banks and online customer complaints.
Keywords: Participation Banking; Coronavirus (Covid -19); Online Complaint; Complaint Management; Content Analysis